Gamification of Virtual Learning Environments: A Narrative and User Experience Approach - Toledo Palomino, Paula; Nacke, Lennart; Isotani, Seiji (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
This research explores the fertile intersection of narrative, gamifica- tion, and education, focusing on user experience (UX). Addressing a critical gap in the literature, we developed and validated a Narrative Gamification Framework for Education. The framework provides educators with tangible guidelines to gamify their lessons, em- phasizing the content’s gameful transformation rather than the environment. Our multi-method research approach spanned a liter- ature review, prototype development, user testing, and validation studies. Results underscored the efficacy of our narrative gamifica- tion strategies in enhancing user engagement and motivation in educational contexts. The research contributes novel insights and practical tools to the fields of Human-Computer Interaction (HCI) and UX, with implications for the broader context of education. Our findings set the stage for future research, including an ongoing initiative to adapt the framework to engage teachers in a journey of recognition and learning.